Statistical findings of time-based stable human aura - S. Z. Nur Eliza; M. Muhazam; W.A. Wan Mat; A. A. Hardy; M. N. Elya; O. Ainsah; A. Miskon; M. Sharil S (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Aura is an electromagnetic field located outside living things which has a number of vibrational energy waves in it. For human being, this vibrating energy waves are related to energy level of the mind, the individual’s emotion and physical. The measurement of this energy can be made indirectly usingbiomedical devices like biosensor instead of direct snapping by optical camera. The aura pattern of the individual involved can be monitored by video capturing of the output produced by the device. Since the subject’s feelings affect aura readings, his emotion will be put to a level as low as possible through a simplemeditation. The data however, will be captured even before meditation to see the changes in the aura pattern and to find if there is any convergence to a stable or a final stage aura. This is what we define as the pure or characteristic aura of the individual. The stable or pure aura might be a little different fromsession to session but within the statistically accepted range. A sample of 10 students regardless of gender had been taken their aura color and analyzed at solar plexus chakra. The personal details of them had also been taken. Some repeated and stable aura images had been observed. It is found that almost everyone has a stable aura regardless of how unstable his aura normally. In general, good students tend to have a more stable aura compared to those with lower academic performance